2021
DOI: 10.1136/bmjopen-2020-047072
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of the Midwifery Initiated Oral Health-Dental Service programme in Australia

Abstract: ObjectivesTo critically evaluate the cost-effectiveness of the Midwifery Initiated Oral Health-Dental Service (MIOH-DS) designed to improve oral health of pregnant Australian women. Previous efficacy and process evaluations of MIOH-DS showed positive outcomes and improvements across various measures.Design and settingThe evaluation used a cost-utility model based on the initial study design of the MIOH-DS trial in Sydney, Australia from the perspective of public healthcare provider for a duration of 3 months t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
(40 reference statements)
0
12
0
1
Order By: Relevance
“…Even without access to dental services; however, oral health advice can still provide a protective effect to a pregnant woman's oral health. A recent study in Australia among pregnant women found that oral health knowledge delivered by midwives was effective in improving oral health even without a clear referral pathway in the short term [21]. As suggested in the ndings, this advice could also be more effectively delivered among Aboriginal and Torres Strait Islander women if culturally appropriate oral health promotion resources are complemented with oral health products.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Even without access to dental services; however, oral health advice can still provide a protective effect to a pregnant woman's oral health. A recent study in Australia among pregnant women found that oral health knowledge delivered by midwives was effective in improving oral health even without a clear referral pathway in the short term [21]. As suggested in the ndings, this advice could also be more effectively delivered among Aboriginal and Torres Strait Islander women if culturally appropriate oral health promotion resources are complemented with oral health products.…”
Section: Discussionmentioning
confidence: 89%
“…These follow up evaluations are important to measure to determine the long-term health and economic impact of the Grinnin' Up Mums & Bubs model of care. Previous evaluations on the e cacy and cost-effectiveness of the MIOH model of care have established that it can reduce dental treatment costs in the long term [21], although more research is needed to determine the long-term impact of the Grinnin' Up Mums & Bubs model. In terms of long-term sustainability, there is also the need to consider the policy barriers that impact on the effectiveness of the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These follow-up evaluations are important to measure to determine the long-term health and economic impact of the Grinnin’ Up Mums & Bubs model of care. Previous evaluations of the efficacy and cost-effectiveness of the MIOH model of care have established that it can reduce dental treatment costs in the long term [ 21 ], although more research is needed to determine the long-term impact of the Grinnin’ Up Mums & Bubs model.…”
Section: Discussionmentioning
confidence: 99%
“…The MIOH intervention was found to be effective in increasing the knowledge and confidence of midwives to promote oral health as well as improving maternal oral health and the uptake of dental services during pregnancy [ 18 ]. The intervention was also widely acceptable and feasible for all stakeholders [ 19 , 20 ], effective in increasing the uptake to dental services during pregnancy, improved the maternal oral health of pregnant women [ 17 ], and was cost effective for health services [ 21 ]. The World Health Organization has recently included the MIOH model in their 2021 implementation guidance document as a case study to showcase integration of oral health into primary health care [ 22 ].…”
Section: Introductionmentioning
confidence: 99%